2021
DOI: 10.1038/s41598-021-92936-z
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap atomistic calculations on hydrogen-passivated GeSi nanocrystals

Abstract: We present a detailed study regarding the bandgap dependence on diameter and composition of spherical Ge-rich GexSi1−x nanocrystals (NCs). For this, we conducted a series of atomistic density functional theory (DFT) calculations on H-passivated NCs of Ge-rich GeSi random alloys, with Ge atomic concentration varied from 50 to 100% and diameters ranging from 1 to 4 nm. As a result of the dominant confinement effect in the DFT computations, a composition invariance of the line shape of the bandgap diameter depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Thus, SWIR spectral sensitivity (cut-off wavelength) was pushed up to 1700 nm for cooled structures (100 K), and up to 1400 nm at room temperature [25], in comparison with Ge NCs embedded in TiO 2 for which a cut-off of 1250 nm was obtained [23]. Density functional theory (DFT) computations of the energy gap of alloy GeSi NCs with high Ge content for finding bandgap diameter dependence for different Ge contents and bigger diameters in agreement to the experimental data can be used for the design and characterization of GeSi NCs-based optical sensors [32]. Based on all these results, recently, we developed an optical sensor system with a photoactive layer of GeSi NCs in the SiO 2 matrix that discriminates between different slippery road conditions, to be mounted on a platform for warning drivers in due time and at sufficient distance [33].…”
Section: Introductionmentioning
confidence: 78%
“…Thus, SWIR spectral sensitivity (cut-off wavelength) was pushed up to 1700 nm for cooled structures (100 K), and up to 1400 nm at room temperature [25], in comparison with Ge NCs embedded in TiO 2 for which a cut-off of 1250 nm was obtained [23]. Density functional theory (DFT) computations of the energy gap of alloy GeSi NCs with high Ge content for finding bandgap diameter dependence for different Ge contents and bigger diameters in agreement to the experimental data can be used for the design and characterization of GeSi NCs-based optical sensors [32]. Based on all these results, recently, we developed an optical sensor system with a photoactive layer of GeSi NCs in the SiO 2 matrix that discriminates between different slippery road conditions, to be mounted on a platform for warning drivers in due time and at sufficient distance [33].…”
Section: Introductionmentioning
confidence: 78%
“…Hydrogen passivation (saturate the surface bonds in the c-direction with −H groups) was applied to stabilize the structures, which has proven to show minimal effects on the calculated band structures and bandgap energies. 83,84 First, the charge density difference and Bader charge analysis revealed that an increased charge accumulation around the interfacial S atoms can be obtained for the heterojunction ZnS-Au 2 S structure as compared to that for the pure ZnS and Au 2 S configurations (Figure 5a−c). 85 Quantitatively, the charge donation of Au increased from −0.13e to −0.19e, and the S atom accepted a total of around 0.54e from both Au and Zn atoms, doubled the charge accumulation on S atoms compared to the Au 2 S (0.26e) system (Table S8).…”
Section: Charge Carrier Dynamics Of Hncsmentioning
confidence: 99%
“…Additionally, DFT calculations for mainly determining the bandgap energy were performed, that are useful for design and characterization of Ge and SiGe NCsbased photosensitive structures [87].…”
Section: Vis-nir-swir Photosensingmentioning
confidence: 99%